Expeditious Calculations of Technical Electric Power Losses in Networks of 35 kV and Higher in Integrated Power System (IPS) of Belarus - M. Fursanov; A. Zolotoi (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
An algorithmized approach to execution of expeditious calculations of technical electric power losses in networks of 35 kV and higher in the Integrated Power System (IPS) of Belarus has been developed on the basis of performance information accumulated by modern intellectual recording and data storage devices. The paper shows that in order to carry out expeditious calculations it is necessary to simulate daily load curves in the non-observable part of the network on the basis of factorial statistical analysis.